Tożsamość kulturowa w perspektywie integracji europejskiej - Stawarz, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2008)
The beginning of the 21st century is the time of a new challenge for the Polish nation. Standing on the threshold of a new century, it has also stood on the ‘threshold’ of the united Europe. Culture is a binder thanks to which it is possible to discover and to maintain peoples’ identity and the bonds connecting individual members of the nation. The multitude of nations is a variety which makes Europe not a monolith in relation to culture; instead, it constitutes a mosaic of different cultures and philosophies of life. The Church does not try to identify with any of the culture patterns, but it seeks its place among the diversity of their forms. However, one can talk about the development of a Christian culture model resulting from the faith and the presence of the evangelical message in the whole of the Christians’ life. In the survey concerning Poland’s accession to the European Union, Polish people have expressed their hopes and fears connected with the process of integration. As many as 11% of the people surveyed expressed their anxiety related to the adverse effect upon culture and customs. The Church in its social instruction continuously emphasizes the necessity of maintaining one’s own cultural identity by particular ethnic, national and regional groups. The united Europe is to become not exactly a federation of countries, but rather the home of homes. In the everyday life of the new united Europe the system of norms, values and patterns of religious and cultural behaviour are going to be verified. Both the sceptics and the enthusiasts of the integration process are looking for a place and a role for the Polish Christians in the secularized European society.